Regulating Polygamy in Muslim States: A Normative and Comparative Study of Marriage Law and Justice - Muhammad Saputra; Zulfikri Zulfikri; Ibnu Radwan Siddik Turnip; Rahmad Efendi (Jurnal Hukum Keluarga, 2025)
Polygamy remains one of the most dynamic and contested issues in Islamic family law, with regulatory frameworks varying significantly across Muslim states. This article examines the regulation of polygamy in the marriage laws of Muslim countries, with a primary focus on Asia and Africa, in order to identify prevailing patterns of restriction, conditional authorization, and prohibition. Employing a normative and comparative legal approach, the study draws on national legislation, judicial decisions, and relevant scholarly literature from journals and academic books. The analysis is conducted through a descriptive-analytical method by examining the principles of Islamic law and their implementation within the positive legal systems of different states. The findings demonstrate that polygamy regulation in Muslim countries generally falls into three dominant models: permissibility subject to strict legal limitations, conditional permissibility under strong judicial supervision, and total prohibition. These regulatory models reflect ongoing efforts by Muslim states to reconcile the normative legitimacy of Sharīʿah with the demands of gender justice and contemporary family law reform. This study argues that the maqāṣid al-Sharīʿah approach plays a pivotal role in the transformation of modern Islamic family law by reorienting marriage law policies toward substantive justice and the protection of women’s rights.